A dairy management system for The University Field Station (UFS) that employs a service-oriented architecture and mobile voice data entry mechanism - Karleen, Lall (My University, 2013)
The aim of this research project is to build a Dairy Management Information System for the Dairy parlour operations at the University Field Station (UFS). One of the major challenges in the Dairy Cattle Milking operations is the proper and timely collection and entry of data on a daily basis. This research seeks to solve this issue through employing a mobile voice mechanism for data entry. A Service Oriented Architecture (SOA) framework is also proposed to enable remote access and to support more efficient collection and management of data in the UFS Field Management System.
Keywords: Management information systems; Dairy plants – Data processing; Service-oriented architecture (Computer science); Dairy farming; Milk yield